1996
DOI: 10.1016/0887-6177(95)00049-6
|View full text |Cite
|
Sign up to set email alerts
|

A clarification of the Russell, Neuringer, and Goldstein process key: Implications for outcome

Abstract: The purpose of this study was that of attempting to clarify discrepant results regarding classificatory accuracy of the Russell, Neuringer and Goldstein (1970) Process Key. The Process Key is the component of the neuropsychological keys that classifies cases as having recently or remotely acquired brain damage on the basis of level of performance and severity of lateralizing signs. A correct classification of acute brain damage occurs when onset of illness began within 3 months of time of testing. A study of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…There was specific documentation of localized involvement of the anterior or posterior cerebral arteries in only 8 patients, although this may be an underestimate because specification of the artery was not often accomplished before availability of the CT scan and MRI. In a previous publication utilizing these patients (G. Goldstein, Shemansky, Beers, George, & Roberts, 1996), it was reported that 48 patients had thrombotic or hemorrhagic strokes and 52 had other forms of stroke, including embolism, aneurysms, and ruptured arteriovenous malformations. Fifty-one of these patients had sustained their strokes within 90 days of testing, and 49 had had their strokes 1 year or more prior to testing.…”
Section: Participantsmentioning
confidence: 99%
“…There was specific documentation of localized involvement of the anterior or posterior cerebral arteries in only 8 patients, although this may be an underestimate because specification of the artery was not often accomplished before availability of the CT scan and MRI. In a previous publication utilizing these patients (G. Goldstein, Shemansky, Beers, George, & Roberts, 1996), it was reported that 48 patients had thrombotic or hemorrhagic strokes and 52 had other forms of stroke, including embolism, aneurysms, and ruptured arteriovenous malformations. Fifty-one of these patients had sustained their strokes within 90 days of testing, and 49 had had their strokes 1 year or more prior to testing.…”
Section: Participantsmentioning
confidence: 99%